Anti-fibrinolytic agents in post partum haemorrhage: a systematic review - Blackhall Karen; Sydenham Emma; Roberts Ian; Ferrer Pili; Shakur Haleema (BMC, 2009)
Abstract Background Post partum haemorrhage is a leading cause of maternal death worldwide. It also contributes to maternal morbidity as women may require a hysterectomy to control bleeding, or may require a blood transfusion, which can transmit viral infections. Anti-fibrinolytic agents have been proposed as a treatment for post partum haemorrhage. We conducted a systematic review to assess the effectiveness and safety of anti-fibrinolytic agents in post partum bleeding. Methods All randomised controlled trials of anti-fibrinolytic agents given for bleeding during the postpartum period were included in this review. We searched Medline, PubMed, EMBASE, Cochrane Central Register of Controlled trials, Web of Science, metaRegister of controlled trials, LILACS, Reproductive Health Library, African healthline, POPLINE, MedCarib, CINAHL, Clinicaltrials.gov and the reference lists of eligible trials. Two authors extracted data. Methodological quality was assessed by evaluating allocation concealment. The primary outcome was maternal mortality. Secondary outcomes were blood loss, blood transfusion, hysterectomy, mean haemoglobin concentration, thrombo-embolic events and other adverse effects. Results We identified three randomised controlled trials involving 461 participants. The trials compared tranexamic acid with no treatment and reported blood loss after delivery. In all three trials, allocation concealment was either inadequate or unclear. The administration of tranexamic acid was associated with a reduction in blood loss of 92 millilitres (95%CI 76 to 109). The most frequently reported adverse effect of tranexamic acid was nausea, although the increase was easily compatible with the play of chance (RR 4.63, 95%CI 0.23 to 95.14). Conclusion Tranexamic acid may reduce blood loss in post partum haemorrhage. However, the quality of the currently available evidence is poor. Adequately powered, high quality randomised controlled trials are needed.